’n Toets vir Gereformeerde Ekumene - J. L. Helberg (In die Skriflig, 1991)
While there is a universal interest for ecumenical involvement, the Reformed Churches in South Africa (GKSA) suspended relations with the Reformed Ecumenical Council, the only ecumenical movement in which the GKSA has ever been involved. Criticism has been directed at the GKSA for isolating itself and for not being concerned in the relevant problematics of the day. This article indicates what the official relations of the GKSA are, how the GKSA approaches the ecumenical calling in the present situation, what problems exist in this regard, and with what test the GKSA is confronted. In order to do this an attempt is made in this article to determine what the norms for ecumenicity according to the Scriptures are. This approach will be undertaken by examining the central revelation-historical lines which occur in the Old Testament and extend to the New Testament, and by outlining the resulting data about the character and the organisation of the church. It will be demonstrated that the church is essentially concerned with the proclamation of the word and the embodiment of the requirements of the Word: not with impersonal, organisational, technical or other structures but with the personal relation with God, the Creator, Ruler and Saviour of mankind as embodied in his (covenant) people. This is a relation with God in Christ and with the neighbour, in an existential, local context and in universal perspective The test for the GKSA will be whether justice is done to the universal character as well as the confessional character and the personal character of its calling. This threefold relation will especially become clear in the GKSA's handling o f the ecclesiastical set-up in the relation with the other National Synods, from the local level up to the synodical level, because it is especially on the level of these National Synods that a lack in the personal relations or the character of these relations is apparent.